Excellent lubricating behavior of Brasenia schreberi mucilage - Li, Jinjin (Langmuir : the ACS journal of surfaces and colloids, 2012)
The present work reports an excellent lubrication property of an aquatic plant called Brasenia schreberi (BS). To investigate the lubrication characteristics of the BS mucilage, a novel measuring system is designed, and an ultralow friction coefficient about 0.005 between the mucilage and glass surface has been obtained. It is found that the ultralow friction is closely related to the structure of mucilage and water molecules in the mucilage. The microstructure analysis indicates that the mucilage surrounding BS forms a kind of polysaccharide gel with many nanosheets. A possible lubrication mechanism is proposed that the formation of hydration layers among these polymer nanosheets with plenty of bonded water molecules causes the ultralow friction. The excellent lubrication property has a potential application for reducing the friction between a glossy pill coated with such layer of mucilage and people's throats